Влияние температуры термообработки на фазовый состав и структуру образцов из набивной массы на основе ZrO₂, стабилизированного комбинированной добавкой CаO и MgO, на фосфатной связке - Мартыненко, Валерий Владленович; Примаченко, Владимир Васильевич; Шулик, Ирина Германовна; Шишковский, Дмитрий Алексеевич; Варганов, Владимир Валентинович; Карякина, Элеонора Леонидовна; Тишина, Татьяна Георгиевна; Терлецкая, Наталья Карповна (НТУ "ХПИ", 2017)
Для высокотемпературных агрегатов разработана набивная масса на фосфатной связке из плавленого диоксида циркония, стабилизированного комбинированной добавкой, с высокими показателями свойств. Специфика процесса эксплуатации данного вида огнеупоров обусловили необходимость изучения их микроструктуры и фазового состава в зависимости от температуры термообработки. Выполнен комплекс исследований указанных огнеупоров после термообработки при температурах 150 – 2200 °С. Анализ полученных данных позволяет прогнозировать их поведение в процессе эксплуатации.

The PJSC “THE UKRAINIAN RESEARCH INSTITUTE OF REFRACTORIES NAMED AFTER A. S. BEREZHNOY” for use in high-lining units improved manufacturing technology of ramming mass on phosphate binder with the new fused material of zirconium dioxide stabilized with an additive combination of calcium and magnesium oxides, which products are characterized by high levels of properties. However, the microstructure and phase composition of the refractories developed by weight depending on the heat treatment temperature nebyli investigated. The need for these studies due to the specificity of technological conversion process and high-temperature operation units, where this type of refractory used, as well as the behavior characteristics of zirconia refractories in different temperature ranges. Samples of developed mass after heat treatment in the temperature range 150 – 2200 °C were subjected to physical, mechanical, chemical, X-ray diffraction, petrographic and electron microscopic studies. The analysis of the data of the complex of conducted studies allows us to predict the behavior of these refractories during their operation.
Influence of the heat treatment temperature on the phase composition and structure of the samples of the ram mass based on ZrO2 stabilized by the combined addition of CaO and MgO on a phosphate binder
Keywords: микроструктура; диоксид циркония; связка фосфатная; microstructure; zirconium dioxide; phosphate binder